(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article examines various aspects of attacking actions by football players during competitions among players aged 16-17. It highlights the balance between attacks conducted through the center and flanks, as well as instances of shots during critical moments. Additionally, the study discusses combinations involving players during attacking actions